2003
DOI: 10.1111/j.1530-0277.2003.tb04408.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain fMRI Activation Associated with Self‐Paced Finger Tapping in Chronic Alcohol‐Dependent Patients

Abstract: These findings are compatible with motor inefficiency and compensatory alterations of cortical-cerebellar circuits. Further studies are needed to determine whether these deficits recover with prolonged abstinence and how they relate to cognitive inefficiency throughout the clinical course of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 77 publications
4
11
2
Order By: Relevance
“…The group differences observed are less likely due to cerebrovasculature abnormalities or problems in regions subserving motor functioning, as the adolescents with AUD showed normal BOLD response to the finger tapping task. This finding contrasts with that of Parks and colleagues (Parks et al, 2003) who found somewhat abnormal BOLD response during a simple motor task in alcohol dependent adults, suggesting that early in the course of AUD, the neural substrates of motor functions may remain intact, while those of more difficult or complex functions such as working memory could be affected.…”
Section: Discussioncontrasting
confidence: 96%
“…The group differences observed are less likely due to cerebrovasculature abnormalities or problems in regions subserving motor functioning, as the adolescents with AUD showed normal BOLD response to the finger tapping task. This finding contrasts with that of Parks and colleagues (Parks et al, 2003) who found somewhat abnormal BOLD response during a simple motor task in alcohol dependent adults, suggesting that early in the course of AUD, the neural substrates of motor functions may remain intact, while those of more difficult or complex functions such as working memory could be affected.…”
Section: Discussioncontrasting
confidence: 96%
“…Moreover, there were no group differences on RT to first button press for any trial type. Although there has been evidence for motor deficits in ADPs (Parks et al, 2003), we only found a trend toward increased RT for sustained motor activity in the ADPs. Taken together, the behavioral RT results indicate that there was not a motor deficit in the ADPs.…”
Section: Discussioncontrasting
confidence: 92%
“…Several fMRI studies reveal that alcoholics activate either a different neural network (Pfefferbaum et al, 2001; Tapert et al, 2001; Tapert et al, 2004) or activate appropriate regions but more widely (Desmond et al, 2003; Parks et al, 2003) to perform behaviorally (e.g., in terms of accuracy or reaction time) on par with controls. For example, self-paced finger-tapping activated frontocerebellar networks in controls (e.g., anterior cingulate, anterior lobe and vermis of the cerebellum) but only the parietal precuneus in alcoholics (Parks et al, 2010).…”
Section: Brain Structures and Systems Affected In Individuals With Almentioning
confidence: 99%